(3TQM GdbUjOI GdfhfjIs - (3GdbQUj, OGhO Hf eMeO, J (B1160 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj habfG dJMbjb GdYbGjO GdESdGejI hcQefG HJObjb GdeHGMK GdcdGejI ajbhd GdYHO GdabjQ OGhO Hf eMeO GdbGQUj GdMfaj deG cGf Yde GdcdGe CTQa GdYdhe GdEfSGfjI hcGfJ GdQSGdI GdTQjaI GdefXheI GdfhfjI GdJj GdagG GdaGVd GdeMbb NVQ Hc CQOJ Cf CTQMgG TQMG LOjOGs
(3BNQgG (B:s
(3EPG eGJ GdEfSGf GfbWY Yedg EdG ef KdGK (B: (3UObI LGQjI hYde jfJaY Hg hhdO UGdM jOYh dg hbGd (B( (3Ae (B) (3CjGV (B: (3ef Sf SfI MSfI cGf dg CLQgG hCLQ ef Yed HgG (B( (3haj GdCUd dgG (B) (3Edi jhe GdbjGeI ef ZjQ Cf JfbU ef CLhQge TjA Gddge jSQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 334s
(3eYLe GdeDdajf (B1 / 702s
(3cTa GdXfhf (B2 / 1348s
(3gOjI GdYGQajf (B1 / 363s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds